Microparticles reveal cell activation during IVF – a possible early marker of a prothrombotic state during the first trimester - Olausson, Nina; Mobarrez, Fariborz; Wallen, Håkan; Westerlund, Eli; Hovatta, Outi; Henriksson, Peter (Thrombosis and Haemostasis, 2016)
Cell-derived microparticles (MPs) are known to be elevated in a number of diseases related to arterial and venous thromboembolism (VTE), such as acute myocardial infarction, VTE (deep-vein thrombosis and pulmonary embolism) and peripheral arterial disease. IVF-associated pregnancies have previously been shown to be associated with an increased incidence of VTE, mechanisms behind being unknown and sparsely studied. Our objective was to assess cell activation during IVF through analysis of MP levels and phenotype following ovarian stimulation. Thirty-one women undergoing IVF were included and blood samples were collected at down regulation of oestrogen and at high level stimulation with 10- to 100-fold increased endogenous oestrogen levels. MPs were analysed by flow cytometry and phenotyped according to size and protein expression. We found that overall phosphatidylserine positive platelet-, endothelial- and monocyte-derived MPs significantly increased following ovarian stimulation with increased levels of platelet activation markers CD40 ligand and P-selectin. Furthermore, there was an increase in endothelial-derived MPs exposing activation marker E-selectin and monocyte-derived MPs, while neutrophil-derived MPs decreased slightly. In conclusion we found a major increase in MPs and markers indicating cell activation in parallel with the profound oestrogen boost during IVF. To assess whether these changes in MPs are associated with thromboembolic events requires extended longitudinal studies.
Keywords: Cell-derived microparticles; oestrogen; in vitro fertilisation; IVF; venous thromboembolism